Performance of ‘Cadenera’ orange trees grafted on five rootstocks - Allan Ricardo Domingues; Carmen Silvia Vieira Janeiro Neves; Inês Fumiko Ubukata Yada; Rui Pereira Leite Junior; Zuleide Hissano Tazima (Revista Brasileira de Fruticultura, 2018)
Abstract Citriculture is an important alternative for the agribusiness development in the state of Paraná, Brazil. However, the use of a few cultivars of scion and rootstock restricts the harvest period and increases the vulnerability to pests and diseases. This study aimed to evaluate the vegetative growth, production and fruit quality of ‘Cadenera’ orange trees (Citrus sinensis (L.) Osbeck ) grafted on five rootstocks, during nine harvests, under a subtropical environmental condition. The experimental design was randomized blocks with six replications, two plants per plot, and five rootstocks: ‘Rangpur’ lime (C. limonia Osb.), ‘Cleopatra’ (C. reshni hort. ex Tanaka ) and ‘Sunki’ mandarins (C. sunki hort. ex Tanaka (L.) Raf.), ‘Swingle’ citrumelo [C. paradisi Macfad. x Poncirus trifoliata (L.) Raf.], and ‘C-13’ citrange [C. sinensis (L.) Osbeck cv. Pera x P.s trifoliata (L.) Raf.]. Biometric variables, and fruit yield and quality were analyzed. The smallest canopy size was induced by ‘Rangpur’ lime and ‘C 13’ citrange rootstocks. ‘Swingle’ citrumelo and ‘C 13’ citrange provided the highest yields for the ‘Cadenera’ sweet orange trees and were superior to ‘Rangpur’ lime. Trees grafted on ‘C 13’ citrange presented the highest yield and productive efficiency.